An evaluation of pregnant women's knowledge and attitudes about newborn bloodspot screening. (February 2017) - Fitzgerald, Catherine; Heery, Emily; Conneally, Neasa; Linnane, Barry; George, Sherly; Fitzpatrick, Patricia
Abstract: Objectives: research suggests that information provided to parents about newborn bloodspot screening (NBS) can be inconsistent. The majority of international NBS programmes recommend that parents should receive information about NBS in the antenatal period, however prior studies have mostly focused on postnatal women's knowledge, with no quantitative study of women's knowledge in the antenatal period conducted to date. Thus, the aim of this study was to determine if antenatal women received information about NBS in the antenatal period and to evaluate their knowledge and attitudes about NBS. Design/Participants: we conducted a cross-sectional study among antenatal attendees at three maternity hospitals in Ireland. A total of 662 antenatal women (≥36 weeks gestation) were recruited into the study (279 primiparous, 368 multiparous). Women were asked to complete a self reported knowledge and attitude questionnaire about NBS. Findings: primiparity (OR 2.75; 95% CI 1.65, 4.59) lower educational status (OR 1.79; 95% CI 1.02, 3.15) and not having private health insurance (OR 1.84; 95% CI 1.19, 2.85) were independently associated with poor NBS knowledge. Fourteen per cent of antenatal women recalled receiving an information leaflet about NBS, yet over 87 % reported that they would like more information. Thirty four per cent of women agreed that they understand everything they need to know about NBS. Conclusions/Implications for practice: the process of providing women with information about NBS in the antenatal period is inconsistent; consequently their awareness about NBS is limited. To make an informed choice about NBS women require information to be provided in a more structured format. There are many missed opportunities in the antenatal period for maternity care providers to provide women with information about NBS. Our study recommends that healthcare providers should have a more formal and structured approach with regard to the provision of information about NBS in the antenatal period. This could be achieved by incorporating NBS education into antenatal education classes or through multimedia while women are waiting in the antenatal clinic. Healthcare providers may need education about the importance and benefits of providing women with information about NBS in the antenatal period.